PERANCANGAN SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA TOKO CHILDS AQUATIC - Miftahul Ridha; Siti Khofifah; Zulkahfi; Saprudin (Buletin Ilmiah Ilmu Komputer dan Multimedia, 2023)
Because information technology has changed so much over time, more and more innovations have been made to make existing technologies more understandable and more up-to-date. for example, in economics, business, entertainment, and other related fields. It is hoped that all members of society can participate in developing science and technology. Almost all types of businesses to date have used a computerized system. The computerized system is made to provide the best service because efforts to increase finances and satisfying services, especially for Small and Medium Enterprises (SMEs) are urgently needed. This business must present a system that can facilitate seller sales and improve customer service because the system used in this sales effort is still manual. As a result, this activity resulted in the creation of a web-based information system that makes it easier for Childs Aquatic Store customers to view product information and make purchases of these products online.